A Comprehensive analysis of the relationship between off-the-job embeddedness and continuance commitment on Intention to stay: Based on PLS-SEM - Ayesha, Noor; Yuserrie, Zainuddin (Penerbit UMP, 2019)
“Employee’s Intention to Stay” as a term is broadly used in organization surroundings. The administrators must be identifying the importance of their staffs not only inspiring them to stay but also discourage them from seeking better job to another place. Conversely, Job embeddedness is a construct which explain the reason of individual’s choice to stay or leave by considering the community and organizational forces that may retain employee on the workplace. Thus, current study examined the relationship between off-the-job embeddedness, continuance commitment and employee’s intention to stay using a sample of 177 employees of ICT industries. Simple Random probability sampling technique and partial least squares structural equation modeling (PLS-SEM) approach was employed to examine the relationship as drawn by the hypotheses. The findings of this paper discovered that there was a significant positive relation between fit and links dimension of off-the job embeddedness, organizational continuance commitment and intention to stay. These outcomes suggest that organizations like ICT industry (technology organization) need to consider off-the-job embeddedness relationships along with continuance organizational commitment when developing programs designed to affect intention to stay decisions of members.